Update: Severe Respiratory Illness Associated With Middle East Respiratory Syndrome Coronavirus (MERS-CoV)—Worldwide, 2012–2013 (Am J Transplant, 2013)
A novel coronavirus has been reported as a cause of severe respiratory illness in patients in the Middle East. The implications for transplant patients are unknown but donors and recipients with unexplained severe respiratory illness and travel to the Arabian peninsula may be infected with this virus.